CyberGIS-Compute: Middleware for democratizing scalable geocomputation - Alexander C. Michels; Anand Padmanabhan; Zimo Xiao; Mit Kotak; Furqan Baig; Shaowen Wang (SoftwareX, 2024)
CyberGIS—geographic information science and systems (GIS) based on advanced cyberinfrastructure—is becoming increasingly important to tackling a variety of socio-environmental problems like climate change, disaster management, and water security. While recent advances in high-performance computing (HPC) have the potential to help address these problems, the technical knowledge required to use HPC has posed challenges to many domain experts. In this paper, we present CyberGIS-Compute: a geospatial middleware tool designed to democratize HPC access for solving diverse socio-environmental problems. CyberGIS-Compute does this by providing a simple user interface in Jupyter, streamlining the process of integrating domain-specific models with HPC, and establishing a suite of APIs friendly to domain experts.